Control of an inverter-based Microgrid in islanded operation - BENAMAR, Meriem; Benrahal, Zineb; Rayane, Khaled (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2023)
Nowadays, there is increasing attention on the generation, distribution, and consumption of electricity, and microgrids are emerging as a viable a practical solution. This dissertation aims to explore hierarchical control techniques for two parallel inverter configurations: forming-forming and forming-following. The control process involves multiple levels, beginning with individual voltage or current control for each inverter, techniques such as Droop control are employed to ensure power-sharing between the inverters. Finally, the Droop control method is further enhanced with voltage amplitude and frequency restoration implementation.
Option: Automatic and systems